Antioxidant compounds and activities of the stem, flower, and leaf extracts of the anti-smoking Thai medicinal plant: Vernonia cinerea Less - Nitinet Ketsuwan (2018)
ï¿½ 2017 Ketsuwan et al. Vernonia cinerea (VC) Less has been proposed as a medicinal plant with interesting activities, such as an aid for smoking cessation worldwide. Despite its previous clinical success in smoking cessation by exhibiting reduced oxidative stress, it has not been approved. The aim of this study was to investigate various antioxidant activity and active compounds that have not been approved, including the protective activity in human red blood cells (RBCs), from the stem, flower, and leaf extracts of VC Less in vitro. These extracts were tested for their antioxidant activity in scavenging 1,1-diphenyl-2-picrylhydrazyl (DPPH) radicals and analyzed by high-performance liquid chromatography (HPLC) for their active compounds: total tannin, five catechin (C) compounds (epicatechin gallate [ECG], C, epicatechin [EC] , epigallocatechin gallate [EGCG], and (−)-epigallocatechin [EGC] ), flavonoid, nitrite, nitrate, caffeine, and nicotine. Moreover, antioxidant activities of the extracts were evaluated in 2,2′-azobis(2-amidinopropane) dihydrochloride (AAPH)-treated RBCs. The results showed that the flower and leaf of VC Less had higher activity than the stem in scavenging DPPH radicals. The tannin content in the flower and leaf was higher than that in the stem. The leaf had the highest content of the five catechins (C, EC, EGCG, ECG, and EGC), the same as in the flavonoid, when compared to the stem and flower. Furthermore, the leaf extract had higher nitrate and nitrite than the stem. Nicotine content was found to be higher in the leaf when compared to the flower. In addition, the leaf showed protective activity in glutathione (GSH), malondialdehyde (MDA), and protein carbonyl, with a dose response in AAPH-oxidized RBCs, the same as in standard EGCG. Thus, this study concluded that radical scavenging and antioxidant compounds such as catechins, flavo noid, nitrate and nitrite, and nicotine are present in different VC Less parts and are included in the AAPH-oxidized RBC model.